The Role of Social Capital in Intergenerational Migration among the Lease Islands Community in Ambon City - Prapti Murwani (Khazanah Sosial, 2025)
This study aims to examine the pattern of intergenerational chain migration from the Lease Islands—comprising Haruku, Saparua, and Nusa Laut—to Ambon City, focusing on the pivotal role of social capital in sustaining and reproducing this mobility over time. The research is motivated by the need to understand inter-island migration not merely as an economic response but as a deeply rooted socio-cultural practice embedded in small island communities. The study employs a qualitative approach with an embedded single case study design, involving seven individual migrant case units from different families. Data were collected through in-depth interviews, participant observation, and documentation in both origin and destination areas. Thematic analysis was conducted using a step-by-step coding process, identification of patterns, and interpretation of meaning. The findings reveal that migration from the Lease Islands to Ambon is facilitated by robust social networks that extend beyond immediate kinship, reinforced by values of solidarity, trust, and social obligation. Pioneer migrants act as cultural brokers, providing information, temporary housing, and initial financial support for newcomers. The intergenerational transmission of migration-related values and experiences institutionalizes migration as a cultural pattern. These findings contribute to a broader understanding of internal migration as a community-based adaptive strategy in geographically dispersed yet socio-culturally cohesive island societies. The study offers an original contribution by integrating the concepts of chain mobility and social capital within the underexplored context of eastern Indonesia in both national and global migration discourse.